2020
DOI: 10.1136/heartjnl-2020-316920
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiac rehabilitation and health-related quality of life following acute myocardial infarction

Abstract: ObjectiveTo study the association of cardiac rehabilitation and physical activity with temporal changes in health-related quality of life (HRQoL) following acute myocardial infarction (AMI).MethodsEvaluation of the Methods and Management of Acute Coronary Events-3 is a nationwide longitudinal prospective cohort study of 4570 patients admitted with an AMI between 1 November 2011 and 17 September 2013. HRQoL was estimated using EuroQol 5-Dimension-3 Level Questionnaire at hospitalisation, 30 days, and 6 and 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
3
18
0
2
Order By: Relevance
“…Entretanto, em concordância com os resultados anteriores, essa pesquisa ainda observou que 70,8% da amostra exibiu mais de 1 problema na dimensão do questionário de qualidade de vida (EQ-5D) em 30 dias pós-IAM. 45,8% referiram ainda apresentar maior carga de dificuldade em atividades habituais, problemas com mobilidade (35% dos pacientes), dor (32,9%), ansiedade (30,2%) e autocuidado (13,8%; Hurdus et al, 2020).…”
Section: Discussionunclassified
“…Entretanto, em concordância com os resultados anteriores, essa pesquisa ainda observou que 70,8% da amostra exibiu mais de 1 problema na dimensão do questionário de qualidade de vida (EQ-5D) em 30 dias pós-IAM. 45,8% referiram ainda apresentar maior carga de dificuldade em atividades habituais, problemas com mobilidade (35% dos pacientes), dor (32,9%), ansiedade (30,2%) e autocuidado (13,8%; Hurdus et al, 2020).…”
Section: Discussionunclassified
“…(5) Changes in SPPB score. (6) The incidence rate of clinical endpoint events (cardiovascular events, cardiogenic death, and all-cause death).…”
Section: Primary and Secondary Outcomesmentioning
confidence: 99%
“…The extent of left ventricular (LV) remodeling has been reported to be the major pathological basis associated with the prognosis after AMI ( 3 ). Multiple published studies ( 4 , 5 ) have demonstrated that cardiac rehabilitation (CR), especially exercise-based CR, can significantly improve the prognosis and quality of life in patients with AMI ( 6 , 7 ). Moreover, increasing studies ( 8 , 9 ) have shown that exercise-based CR can reverse LV remodeling in patients with AMI by decreasing LV end-diastolic volume (LVEDV) or LV end-systolic volume (LVESV) and increasing LV ejection fraction (LVEF).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of exercise for mortality reduction after AMI are well known but the effect on HRQoL has received less attention. In this issue of Heart, Hurdus and colleagues 1 examined the temporal association of HRQoL with physical activity levels and cardiac rehabilitation in 4570 patients at 30 days, 6 and 12 months after AMI. Both cardiac rehabilitation and self-reported physical activity of at least 150 min/week were positively associated in improvements in HRQoL at each time point, with an additive effect for physical activity even in those receiving cardiac rehabilitation (figure 1).…”
Section: Catherine M Ottomentioning
confidence: 99%